Comprehensive comparison between photothermal power generation and photovoltaic power generation - LI Fuchun; LIU Fei; SHAO Chengcheng; TIAN Xu; TIAN Weiyi; FENG Bin (电力工程技术, 2024)
Photovoltaic power generation and photothermal power generation are two forms of solar power generation. The development cost of photovoltaic is relatively lower than photothermal, but a certain proportion of energy storage and distributed synchronous condensers are needed to ensure the safe and stable operation of the system. As a result the cost of photovoltaic power generation rises. Photothermal comes with heat storage and output friendliness, so currently there is still a great dispute about the technical route of photovoltaic and photothermal. This paper takes Haixi area of Qinghai province as an example. Firstly, based on the characteristics of solar irradiation resources and output in the same time and space, the power guarantee capabilities of photovoltaic+energy storage and photothermal is compared. Then this paper compares photovoltaic+energy storage+condenser with photothermal from the perspective of power grid security and stability support ability. Finally, this paper compares the economics of solar thermal and photovoltaic based on the forecast of their cost declining trend. Photothermal has both thermal storage and conventional generator functions, providing short circuit capacity, reactive power compensation and moment of inertia support for the system. The results show the economy of photothermal is basically equivalent to, or even better than photovoltaic+energy storage+condenser after the cost reduction in the case of technical equivalence.